Flavonoids from the roots of Sophora flavescens - Quang, Tran Hong; Nhiem, Nguyen Xuan; Tuan Anh, Hoang Le; Tai, Bui Huu; Minh, Chau Van; Kim, Young Ho; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
Phytochemical study on the roots of Sophora flavescens resulted in the isolation of eight compounds. Their structures were identified as isoxanthohumol (1), norkurarinone (2), kurarinone (3), 2¢-methoxykurarinone (4), kushenol T (5), norkurarinol (6), kuraridin (7), and formononetin (8) by detailed analyses of 1D and 2D NMR, and MS in comparison with the data reported in the literature.